THE ROLE OF TEACHER AND PEER IN HELPING THE STUDENTS ORALLY PARTICIPATE IN AN EFL CLASSROOM - Ardianti, Triubaida Maya (Journal of Foreign Language Teaching and Learning, 2017)
The purpose of the study is to discover the role of teacher and peer in helping the students orally participate in an EFL classroom. I applied a three-month qualitative case study on 24 first-year university students. I employed observation, open-ended questionnaire, and in-depth interview to collect data. Further, I applied inductive analysis to decode the data. The results of the study revealed that first, the teacher played an important role to help the students orally participate in both class and group discussions through the inquiries provided during the class discussion, and feedbacks given after the group discussions. Second, results of the study indicated that peers also significantly contributed to motivating the lower-achieving students to improve their oral participation,particularly in group discussions. In this circumstance, the data revealed that the students showed learning enthusiasm which helped creating a positive learning athmosphere in which this positive learning athmosphere can be perceived when they motivated one another through feedbacksgiven to solve their difficulties finding appropriate English terms and pronounciation, arranging their sentence structure, and developing their ideas. In addition, the students motivated one another through fun activities such as talking about movie quotes, and words of encouragement. In short, both teacher and peer helped encouraging the students to orally participate in both class and group discussions.